The Role of the Indonesian Language in Law Enforcement in Indonesia: A Juridical and Sociolinguistic Study - Anita Puspawati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The Indonesian language holds a strategic position in the Indonesian legal system as the state language and official language in the formation and enforcement of law. The use of inappropriate language in legislation and judicial practice has the potential to create multiple interpretations, legal uncertainty, and obstacles to access to justice for the public. This research aims to analyze the role of the Indonesian language in law enforcement in Indonesia and identify linguistic problems that affect the effectiveness of legal implementation. This research uses normative legal research methods with statutory and conceptual approaches, through library research on regulations, legal language guidelines, and relevant legal literature. The research results show that the Indonesian language not only functions as a legal communication tool, but also as an instrument determining the meaning of norms and legal certainty. However, inconsistencies in terminology and unclear formulations of legal language are still found in practice. Hence, strengthening the use of the Indonesian language is needed through standardization of legal terms, improvement of language competence of law enforcement officials, and preparation of clear and communicative legal products in order to realize just and effective law enforcement.